The maintenance method of KTMB railway track / Mohd Redzwan Musa - Musa, Mohd Redzwan (2004)
KTM Komuter is one of the most important public transportation systems in Klang Valley. Its positioning placement needs to be exacting standards as affects the efficiency of movement for the KTM Komuter users. The title of this research is 'THE MAINTENANCE METHOD OF KTMB RAILWAY TRACK' covers a little bit on the aspect of Permanent Way or in other word railway track on maintenance management. Also involves the organization study and concerns the railway track performance which affects the KTM Komuter effectiveness. The study conducted is to analyze the improvement maintenance management or permanent way of KTM Berhad. This is done by conducting an extensive research to determine the categories of railway track system and also the methodology of facilities management associated with KTM Komuter services. The research findings will also include an analysis of arising problems associated to the existing railway track system. Strategies are also suggested and concluded at the end of the overall research as a guide to the management staff of the railway track system. This is so, that re-analysis of current procedures can be done and constructive changes can be made in conjunction with on going facility management practices for an optimal utilization of current KTM Komuter services.